Relasi Ilmu dan Agama Dalam Perspektif Falsafah Ilmu - Anissa Alvi; Rosyidah Nurul Fitriyah; Dyna Shofi Euisya; Fatih Ilham Yonri; Nasikhin; Mahfud Junaedi; Samuel Unwakoly (DIKLINKO JOURNALS PUBLISHER, 2023)
This study aims to analyze the relationship between science and religion from the perspective of the philosophy of science. By using library research methods, this study shows that science and religion have significant differences in approaches to knowledge and reality. Science is knowledge obtained through research and experimentation, while religion binds oneself to God and shapes behavior. However, both have similarities in the desire to seek the truth, recognize human limitations, and try to understand the world. They can synergize in a deeper understanding of life and reality, with similarities in their presumptions, methods and concepts. This study has a positive impact on the development of philosophical scholarship, especially in the study of the relationship between science and religion from the perspective of the philosophy of science.